(untitled) (Semiárida, 2023)
The present work calculates the total and intermediate gross marketing margins (MBC) of the links that make up the commercial channel of fresh pork meat, for a period of 5 years. Costs and prices were collected and structured and ordered as following the sequence of the commercial channel. Prices were deflated to transform them into real prices. The MBC were then calculated for production, industry, distribution and freight, until reaching the price paid by the consumer. Finally, the price received by the producer for the sale of capons of different quality and the price paid by the consumer for different cuts were raised. The results allow us to conclude that, in a scenario of average prices of cuts (integrated price) and before different qualities of carcass, the margins are stable in the order of 29 % for production, 33 % industry and 35 % distribution. By raising awareness about the quality of the capon, the producer obtains a better remuneration, allowing him to capture a greater MBC. However, the largest participation is obtained in a scenario of cheap prices (33 to 38 %). Faced with cuts that are expensive for the consumer, distribution appropriates an MBC greater than 50 %.